2011
DOI: 10.1016/j.ajhg.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Variants Near FOXE1 Are Associated with Hypothyroidism and Other Thyroid Conditions: Using Electronic Medical Records for Genome- and Phenome-wide Studies

Abstract: We repurposed existing genotypes in DNA biobanks across the Electronic Medical Records and Genomics network to perform a genome-wide association study for primary hypothyroidism, the most common thyroid disease. Electronic selection algorithms incorporating billing codes, laboratory values, text queries, and medication records identified 1317 cases and 5053 controls of European ancestry within five electronic medical records (EMRs); the algorithms' positive predictive values were 92.4% and 98.5% for cases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
235
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(245 citation statements)
references
References 65 publications
7
235
0
1
Order By: Relevance
“…16). The 9q22 locus has previously been linked to multiple thyroid-specific diseases including goitre, hypothyroidism and thyroid cancer 48,49 , and loss-of- function mutations in a thyroid-specific transcription factor at this locus, FOXE1 , manifest as ectopic thyroid tissue or cleft palate in developing mice. However, the mechanism of any cis -effects of these trans -eVariants remains uncertain from the GTEx data; a post hoc analysis demonstrated that PEER correction removed broad regulatory signals from the 9q22 locus, and particularly from cis - and trans -eQTL signals for FOXE1 (Supplementary Information 17).…”
Section: Expression Qtls and Complex Disease Associationsmentioning
confidence: 99%
“…16). The 9q22 locus has previously been linked to multiple thyroid-specific diseases including goitre, hypothyroidism and thyroid cancer 48,49 , and loss-of- function mutations in a thyroid-specific transcription factor at this locus, FOXE1 , manifest as ectopic thyroid tissue or cleft palate in developing mice. However, the mechanism of any cis -effects of these trans -eVariants remains uncertain from the GTEx data; a post hoc analysis demonstrated that PEER correction removed broad regulatory signals from the 9q22 locus, and particularly from cis - and trans -eQTL signals for FOXE1 (Supplementary Information 17).…”
Section: Expression Qtls and Complex Disease Associationsmentioning
confidence: 99%
“…We used the Illumina ® Absorption, Distribution, Metabolism and Elimination (ADME) Core Panel (CA, USA) [33] to genotype 6067 European-American and 762 AfricanAmerican patients linked to deidentified electronic health records (EHRs). The EHR is a source of highdimensional clinical data, well suited for studying pleiotropic effects across a wide spectrum of clinical phenotypes [34,35].…”
Section: Future Science Groupmentioning
confidence: 99%
“…Examples of discoveries using EMR-linked DNA biobanks include variants associated with PR segment duration on electrocardiography and variants associated with white blood cell count. [27][28][29] Most eMERGE sites have employed an "opt-in" approach to DNA collection, in which patients with targeted phenotypes are consented for blood collection. An advantage of this approach is that patient identifiers can be maintained, which allows recontact of patients (and potentially family members) for future studies.…”
Section: Emr-linked Biorepositoriesmentioning
confidence: 99%